Purification Performance of Biological Two-staged Plant Sewage Systems (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
In the following article, results regarding purification performance of one of several biological two-staged sewage systems constructed in Poland are presented. The system selected was built for purification of sewage from an environmental center in Pszczew in West Poland. The performance evaluation refers to the elimination of nutrients as well as organic compounds. The results are furthermore compared to legal purification requirements for sewage systems in Poland. Since the purification achieved was so high, the purified sewage water can be used for irrigation purposes of the green area in the grounds of the environmental center all year long. By closing this circle, the ecological effects of the method used for sewage purification are much increased.